2006
DOI: 10.1111/j.1744-7429.2006.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Laughing Falcon (Herpetotheres cachinnans) Predation on Coral Snakes (Micrurus nigrocinctus)1

Abstract: Laughing falcon (Herpetotheres cachinnans) predation on coral snakes (Micrurus nigrocinctus) was recorded in two incidents that illustrate previously unreported variation in predatory behavior. In the first, the falcon held a live coral snake by the posterior end for an extended period of time, rather than decapitating it immediately. In the second, the falcon left a decapitated coral snake in a tree for more than 2 h before returning to recover its prey. A variety of behavioral adaptations may protect laughin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…In fact, even venomous snakes are sometimes preyed by birds (e.g. Laurencio, 2005;DuVal et al, 2006). Recently, Costa et al (2009) reported X. merremii as prey of the laughing falcon, Herpetotheres cachinnans, in a situation similar to that described here.…”
Section: The Vulture Cathartes Burrovianus Preys On the Snake Xenodonmentioning
confidence: 50%
“…In fact, even venomous snakes are sometimes preyed by birds (e.g. Laurencio, 2005;DuVal et al, 2006). Recently, Costa et al (2009) reported X. merremii as prey of the laughing falcon, Herpetotheres cachinnans, in a situation similar to that described here.…”
Section: The Vulture Cathartes Burrovianus Preys On the Snake Xenodonmentioning
confidence: 50%
“…However, we are aware that the evolution of imperfect mimicry may be facilitated by other extrinsic factors like niche preferences, predators with different visual systems (i.e., mammals vs. birds), and biogeographic history in areas with elevated model color diversity, as is the case for Micrurus in western Amazonia (Bosque et al., 2016). There are few cases where predation of coral snakes has been observed in nature (DuVal, Greene, & Manno, 2006) but it has been reported that in one specific site at least 90 species are potential predators of coral snakes (França, 2008). Predators of coral snakes have sufficient opportunity for social learning, given the number of species in a particular area (interspecific leaning) and the various degree of sociality of each species, ranging from less social species (red‐legged seriema Cariama cristata ), to highly social species (greater ani, Crotophaga major ).…”
Section: Discussionmentioning
confidence: 99%
“…The Laughing falcon (Herpetotheres cachinnans) is a raptor bird with a wide distribution from Mexico to Argentina, inhabiting forests edges and open areas with isolated trees (Thiollay 1994;Castroviejo and Ibañez 2005). Its diet comprises a variety of organisms like arthropods, anurans, lizards, birds, rabbits, rodents, bats, and fishes but they mainly feed on snakes, including large and poisonous ones (DuVal et al 2006;Costa et al 2010;Specht et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning venomous snakes, there is limited knowledge of identified species preyed on by this falcon, although published articles report predation on Crotalus durissus, Bothriechis schlegelii, Bothrops asper, Micrurus nigrocinctus, M. lemniscatus (Specht et al 2013;Laurencio 2005;Sasa et al 2009;DuVal et al 2006;Sazima and Abe 1991). Nevertheless, insufficient information has come to light concerning the way they adopt to predate venomous snakes.…”
Section: Introductionmentioning
confidence: 99%